Kinerja Keuangan dan Strategi Cash Holding Pada Perusahaan Artificial Intelligence (Ai) di Dunia: Menelaah Pengaruh Moderasi Dari Ukuran Perusahaan - Amalia, Cut Intan; Liza, Laisa; Ivana, Farah (Worksheet : Jurnal Akuntansi, 2025)
This study aims to evaluate the influence of Return on Asset (ROA) and Return on Investment (ROI) on cash holding in global AI companies, considering firm size as a moderating variable. Employing a quantitative approach with associative hypothesis testing, the study was conducted on 13 prominent AI firms listed on stock exchanges in their respective countries. The sample was selected through a saturated sampling technique (census) covering the period from 2020 to 2024. Data analysis was performed using IBM SPSS 27 software to test the hypotheses with Moderation Regression Analysis (MRA). The results indicate that ROA does not have a significant effect on cash holding, either directly or through the moderating role of firm size. Conversely, the influence of ROI on cash holding shows a significant difference when firm size serves as a moderating variable. Although ROI does not have a significant direct effect, the relationship becomes significant through the moderation of firm size.